Pseudolumen Size and Perimeter in Prostate Cancer: Correlation with Patient Outcome - Kenneth A. Iczkowski; Kathleen C. Torkko; Gregory R. Kotnis; R. Storey Wilson; Wei Huang; Thomas M. Wheeler; Andrea M. Abeyta; M. Scott Lucia (Prostate Cancer)
We demonstrated in 2011 that 61% of men with postoperative PSA failure had some cribriform pattern of prostate cancer, versus 16% of nonfailures ( OR=5.89, 𝑃<.0001). That study used digitized radical prostatectomy slides from 153 men, 76 failures (≥0.2 ng/mL) matched to 77 nonfailures. The current study's hypothesis: pseudolumen size and shape variability could stratify outcome within histologic patterns (single separate acini, separate acini with undulating lumens, fused small acini, papillary, cribriform). Pseudolumens were filled digitally on image captures from previously annotated specimens. Among all 5 patterns, pseudolumen spaces averaged smaller in failures than nonfailures. After multivariate analysis controlling for stage, age, margin, cancer amount, prostate volume, and presence of individual cells (grade 5), this retained significance only for the undulating-lumens and papillary patterns. In undulating-lumens pattern, PSA failures had smaller mean pseudolumen space sizes (𝑃=.03) but larger perimeters (𝑃=.04), implying more pseudolumen irregularity. In papillary pattern, the number of pseudolumen spaces was higher in failures (𝑃=.015), space size was smaller (𝑃=.11), perimeters were smaller (𝑃=.04), and perimeter/size ratio was higher (𝑃=.02). In conclusion, digitally measured pseudolumen size and shape may associate with outcome.